Hydrogen-bond interactions in morpholinium bromide - Padayachy, Kamentheren (International Union of Crystallography, 2011)
In the title compound, C(4)H(10)NO(+)·Br(−), which was synthesized by dehydration of diethanolamine with HBr, morpholinium and bromide ions are linked into chains by N—H⋯Br hydrogen bonds describing a C (2) (1)(4) graph-set motif. Weaker bifurcated N—H⋯Br interactions join centrosymmetrically related chains through alternating binary graph-set R (4) (2)(8) and R (2) (2)(4) motifs, to form ladders along [100]. In addition, C—H⋯O interactions between centrosymmetric morpholinium cations link ladders, via [Image: see text](8) motifs, to yield sheets parallel to (101), which in turn are crosslinked by weak C—H⋯O interactions, related across a glide plane, to form a three-dimensional network.